Faith abroad: how religion shapes Trump administration’s foreign policy - Ülgül, Murat (International relations, 2021)
Religion has always been an important factor in American foreign policy. From the ‘holy wars’ against the Indians in the pre-independence period to the ‘crusade’ against Iraq in 2003, faith and religion have shaped the policies of American administrations in all periods. As Bonnell observed in 1971, ‘without a single exception. . .all presidents have publicly avowed their trust in God’. And even if the president was not a religious individual before moving to the White House, Billy Graham noted, they all ‘left the presidency with a very deep religious faith’. The same can be applied to Donald Trump whose presidency witnessed important domestic and foreign policy decisions that can be linked to religious motives. This is especially clear when one takes into consideration that around three-fourth of evangelicals and born-again Christians voted for him in the elections and Trump’s statement before the House elections that ‘nobody’s done more for Christians and evangelicals’ than him. This study will analyze the religious characteristics of Donald Trump and the members of his foreign policy team, such as Mike Pence and Mike Pompeo, and how their religious identity affected the foreign policy decisions of the Trump administration.